Child‐Care Subsidies and Child‐Care Choices Over Time. Issue 5 (11th June 2014) - Johnson, Anna D.; Martin, Anne; Ryan, Rebecca M.
<x xml:space="preserve">Abstract</x> The evidence to date on the federal child‐care subsidy program's effect on preschool child‐care quality is mixed. However, an as‐yet untested outcome of subsidy receipt is subsequent child‐care choice. Specifically, it is possible that subsidy receipt in toddlerhood increases the likelihood of attending other publicly funded preschool programs—Head Start and public pre‐k—that provide the highest quality care available to low‐income families. Using data from the Early Childhood Longitudinal Study–Birth Cohort (n ≈ 2, 100; approximately 2 years old), this study finds that subsidy receipt during toddlerhood predicts greater use of the other forms of publicly funded care in the preschool year, although only if the earlier subsidy is used in a center. These results highlight a previously unconsidered potential benefit of the subsidy program.